Adherence With Bisphosphonates and Long-Term Risk of Hip Fractures: A Nested Case-Control Study Using Real-World Data. (September 2017) - Shalev, Varda; Sharman Moser, Sarah; Goldshtein, Inbal; Yu, Jingbo; Weil, Clara; Ish-Shalom, Sophia; Rouach, Vanessa; Chodick, Gabriel
Background: Hip fracture is a major complication of osteoporosis. Bisphosphonate medication is the mainstay of treatment for osteoporosis. However, concerns have been raised regarding the effectiveness of bisphosphonates in reducing hip fracture risk after long-term use, particularly among patients with suboptimal adherence.Objective: To examine the association between adherence with bisphosphonate therapy and long-term risk of hip fracture.Methods: Included in the present nested case-control study were osteoporotic women (n = 14 357) who initiated bisphosphonate therapy in 2000-2010 and were retrospectively followed for incident hip fracture through November 2014. Within this cohort, each case of primary hip fractures was individually matched to 3 controls without a primary hip fracture. Proportion of follow-up days covered (PDC) with bisphosphonates was calculated from bisphosphonate purchases. Adherence was categorized into the following groups: purchase of 1 or 2 months' supply (reference group), at least 3 months' supply to PDC ≤20%, PDC >20% to ≤80%, PDC >80% to ≤100%.Results: Included in the analysis were 426 case-control groups with a mean age (SD) of 73.7 years (7.9). Compared with the reference group, PDC of 80% to 100% with bisphosphonates was associated with a significant reduction in hip fracture risk for patients with 8 to 15 years of follow-up (OR = 0.39; 95% CI = 0.18-0.87). Among patients with a follow-up of up to 3 years, OR was 0.58 (95% CI = 0.31-1.06).Conclusions: Adherence with bisphosphonates among osteoporotic patients is associated with lower risk of hip fracture, with no indication of diminished effectiveness with long-term use.